CHARACTERISTIC OF CARSINOMA MAMMAE AT RSUD DR. H. ABDUL MOELOEK BANDAR LAMPUNG 2010-2012 - Utami, Vicki Lusbiyanti; Muhartono, Muhartono; Fiana, Dewi Nur; Soleha, Tri Umiana (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Background: Tumor is a neoplastic condition, means the local tissue is overgrowth and incoordinated through the stimulus that triggers the growth has ceased. Histopathological examination is the gold standard method to determinate and diagnose tumors. This examination distinguish the degree of malignancy of a tumor, whether leading to a benign or malignant changes. Currently, breast tumor is one of the neoplasm most often found, especially for malignant tumor, and cause high mortality in the world. The aim of study is to find out the histopathological type of the breast tumor. Methods: The method of this descriptive study is cross sectional, which is conducted in the Anatomical Pathology Installastion In Doctor Haji Abdul Moeloek General Hospital, Bandar Lampung. Data collecting procedure was carried out by analyses to each 75 data of medical records of breast tumor histopathology type during 2010-2012, using total sampling method. Histopathological type obtained then grouped by the World Health Organization 2003 classifiation. Results: The results of this study indicate that the type of the most breast tumor histopathology on the Anatomical Pathology Installation in Doctor Haji Abdul Moeloek General Hospital, Bandar Lampung, during 2010-2012 is fibromadenoma mammae as the most benign mammary tumors of 30 people (40%) and malignant tumor which is 45 people (60%). Conclusion: Fibroadenoma mammae is the most benign mammary tumor and invasive ductal carcinoma mammae is the most malignant mammary tumor in Anatomical Pathology Installation at Doctor Haji Abdul Moeloek General Hospital, Bandar Lampung, during 2010-2012. [J Agromed Unila 2014; 1(1):1-7] Keywords: breast tumor, descriptive, histopathology